EFFECT OF OPTIMIZED MINERAL FERTILIZATION ON YIELD AND STRUCTURAL ELEMENTS OF WINTER WHEAT ON THE RETISOL OF WESTERN POLISSIA OF UKRAINE - Yashchenko, Liudmyla (Journal of Agricultural Sciences (Belgrade), 2025)
The effects of mineral fertiliser rates, based on removal NPK by grain and grain+straw, compared with the recommended rate on winter wheat (Triticum aestivum l.) crop productivity were studied. The treatments were done in the background of different ameliorants with plant residue returns to the soil. In Retisol the highest winter wheat grain yield (4.98 t ha-1) was obtained with the application of 1.0 Hh (hydrolytic acidity) rate of dolomite lime (DL) with N150P50K125 (rate based on grain and straw NPK removal). This treatment led to the best indicators of yield structure elements. However, the harvest index was lower than with N130P25K35 (rate based on grain NPK removal). This suggests a higher grain-to-straw ratio with the NPK removal-only grain-based approach. Despite lower structural indicators, the average yield in treatment with DL (1.0 Hh) + N130P25K35 had no statistically significant difference compared to the N120P60K90 (recommended rate) at P<0.05 The absence of PK fertilizers in treatment with N130, significantly decreased yield (19%) compared to the other NPK treatments. Applying 1.0 Hh limestone (LS) with the recommended NPK rate did not promote the formation of structural elements, and the yield decrease was 0.21 t ha-1 compared to DL (1.0 Hh) under similar conditions. Based on the results, applying mineral fertilizer rates calculated by main product (grain) NPK removal, combined with 1.0 Hh DL and the return of plant residues to the soil, is recommended for optimal winter wheat productivity on Retisols.